STRESS ANALYSIS OF SUSPENSION BRACKETS ON A 12-METER ELECTRIC BUS USING THE FINITE ELEMENT METHOD - Rifky Zaidani; Mochamad Mas'ud (Media Mesin: Majalah Teknik Mesin, 2023)
One of the optimization techniques that can be carried out by an engineer in designing a vehicle chassis is to reduce the weight of the chassis itself while still considering several performance targets that must be met, especially in terms of vehicle safety. In this article the author uses the Finite Element Method (FEM) to determine the strength of a component that plays an important role in determining vehicle safety, namely the Rear Axle Suspension Bracket using Ansys and Inventor to create a 3D model of the component, then the author compares the 2 bracket models with the type of material and thickness which was made to find out the stress of the material. One of the parameters that the author uses in determining the Design safety of the two bracket models is the Factor of Safety, Deformation, and Equivalent Elastic Stress values. The results that the authors get showed that the value of the Factor of Safety of bracket Model 1 with the same material as the bracket Model 2, that is 6 mm thick plate is 1.48 or still within the value required by PT. INKA is 1.4 to 1.8 and for the Equivalent Elastic Stress value of 166 MPa or still below the maximum value limit for SS400 material, which is 250 MPa.